The role of taxpayers’ education in mediating the relationship between tax sanctions and taxpayers’ motivations to use e-filling - I Gusti Ayu Agung Omika Dewi; Yudi Prihandono (Universitas Pendidikan Nasional, 2020)
This study aimed to test empirically the effect of taxpayers’ educational status on the correlation between the taxpayers’ perceptions about tax sanctions and taxpayers’ willingness in reporting tax using e-Filling. This study used taxpayers’ educational status as a moderated variable, taxpayers’ perceptions about tax sanctions as an independent variable, and taxpayers’ willingness in reporting tax using e-Filling as a dependent variable. This study used primary data that are collected by using a questionnaire with incidental random sampling as the sampling technique. The sample of the research is the taxpayers domiciled in South and East Denpasar. Since South and East of Denpasar are the service area of KPP Pratama East Denpasar. The sample of this research was100 people. The data analysis of this research used Statistical Analysis Method using Moderated Regression Analysis. The results of the research show that the taxpayers’ perception of tax sanctions has a significantly positive effect on the taxpayers’ willingness in reporting tax using e-Filing and the level of taxpayers’ educational status has a significantly negative effect on the relationship between taxpayers’ perceptions about tax sanctions and taxpayers’ willingness in reporting tax using e-Filling.